Sex Alphabet - Hao, Julia (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
A creative and hybrid retelling of a young woman’s life, from childhood to early adulthood, after her early exposure to pornography. Narrated in fragments through each of the letters of the alphabet, we follow the young woman’s journey to healing and love as she first struggles with pornography addiction, body dysmorphia, self-harm, and faith and against predatory relationships.